Low Carbon Practices In Households - Mahat, Hanifah; Anak Pasang, Doreen; Hashim, Mohmadisa; Saleh, Yazid; Nayan, Nasir (Journal of Techno-Social, 2019)
In order to address the issue of climate change and global warming, scientists and policy makers all around the world suggest that a drastic reduction in the consumption of electricity to be carried out. Low carbon practices undertaken by households, such as saving electricity is a good effort for the survival of future generations. This is because households are seen as an important target group for energy conservation. Thus, this study aimed to see the difference of income with the usage of electrical appliances and relationship between the usage of elctrical appliances and household energy saving practioces. Methodology of this study was completely based on questionnaire involving 400 respondents representing households and were selected using random sampling techniques. The results of ANOVA test shows there is a significant difference between income varible with the usage of electrical apliances which income variable (F= 10.311 with p < 0.05). The study also found that the use of electrical appliances by households has a negative and weak relationship with household energy saving practices. The findings from this study clearly show that through the difference in income, energy usage pattern of electrical appliances by households also has changed. Thus, if the awareness of saving electricity is not practiced among householders, global warming and climate change will be a long-term issue that will concern the various parties. Â Keywords: Low Carbon practices, households, electric appliances used, income, energy saving behaviour